Analysis of transport performance indicators - Išoraite, Margarita (Transport, 2005)
The article analyses the following issues: 1) key performance indicators, 2) best value indicators, 3) performance indicators and the change process, 4) transport programme indicators inputs, outputs, results and impacts, 5) indicators of effectiveness, efficiency and performance, 6) overcoming of the problems of using indicators, 7) criteria of the establishment of performance indicator system.First Published Online: 27 Oct 2010